Methodological Foundations and Effectiveness of the CLIL (Content and Language Integrated Learning) Approach in Teaching English Based on Cultural Content within Tourism Education - Shodiyeva , Nilufar Olim qizi (The Lingua Spectrum, 2026)
This article analyzes the methodological foundations and effectiveness of teaching based on CLIL (Content and Language Integrated Learning), which is considered one of the modern educational approaches in the rapidly developing field of tourism. The article presents the main approach of the research work, including CLIL and its theoretical foundations, practical application experiences, and experimental analyses. Students do not learn the language separately; instead, the language learning process occurs naturally and effectively. Learners begin to use the language in practice and develop communicative competencies. Greater emphasis is placed only when encountering complex grammatical structures or language elements. The relevance of this methodology for the tourism sector and its effectiveness in developing cultural competencies are also highlighted. Topics and discussions organized within the framework of cultural content enhance students’ ability to exchange ideas, justify their viewpoints, and think freely, thereby improving their social and communicative skills. Furthermore, it is emphasized that through the CLIL approach in teaching English based on cultural content, students learn the language naturally and meaningfully, increase their motivation, develop intercultural competence, and strengthen communicative skills.